An international multicentre randomised controlled trial of en bloc resection of bladder tumour vs conventional transurethral resection of bladder tumour: first results of the en bloc resection of urothelium carcinoma of the bladder (EBRUC) II trial - Struck, Julian Peter; Moharam, Nadim; Leitenberger, Armin; Weber, Jörg; Lusuardi, Lukas; Oswald, David; Rassweiler, Jens J; Fiedler, Marcel; Horňák, Jakub; Babjuk, Marek; Micali, Salvatore; Zaraca, Carlo; et al. (BJU international, 2025)
OBJECTIVES: To determine the safety and oncological advantages of en bloc resection of bladder tumour (ERBT) vs conventional transurethral resection of bladder tumour (cTURBT) in terms of resection quality, staging quality, and safety. PATIENTS AND METHODS: We conducted a single-blinded randomised controlled trial at seven European hospitals with the following inclusion criteria: first diagnosis of non-muscle-invasive bladder cancer, no singular carcinoma in situ, and tumour size >4.3 mm. Patients were randomised intraoperatively in a 1:1 ratio to either the ERBT or cTURBT group. Outcome analysis was performed using the chi-square test, t-test, and multivariate regression analysis. RESULTS: A total of 97 patients were randomised into the study (cTURBT = 40, ERBT = 57). A switch to cTURBT was necessary in two patients (3.5%) and 11.5% of the screened patients were preoperatively excluded for ERBT. There was no difference in the specimen presence of detrusor muscle with 73.7% in cTURBT and 67.3% in ERBT specimens (P = 0.69). There were no significant differences in mean operative time (ERBT 27.6 vs cTURBT 25.4 min, P = 0.450) or mean resection time (ERBT 16.3 vs cTURBT 15.5 min, P = 0.732). Overall the complication rate did not differ significantly (ERBT 18.2% vs cTURBT 7.5%, P = 0.142). Bladder perforations occurred significantly more often in the ERBT group (ERBT seven vs cTURBT none, P = 0.020). R0 status was reported more often after ERBT, whilst a second resection was significantly less frequent after ERBT (P = 0.018). Recurrence rates were comparable for both techniques after 6 months of follow-up. CONCLUSION: The feasibility of ERBT is higher than previously reported. Whereas other perioperative and safety parameters are comparable to cTURBT, bladder perforations occurred significantly more often in the ERBT group and raised safety concerns. This is why this trial was terminated.
Keywords: senioři; EBRUC II; Transurethral Resection of Bladder; senioři nad 80 let; nádory močového měchýře; výsledek terapie; Single-Blind Method; Middle Aged; mužské pohlaví; jednoduchá slepá metoda; Cystectomy; transurethral resection of bladder tumour; Aged, 80 and over; ženské pohlaví; Humans; lidé středního věku; Urinary Bladder Neoplasms; non‐muscle‐invasive bladder cancer; transuretrální resekce močového měchýře; Female; Aged; en bloc resection; bladder cancer; Treatment Outcome; lidé; Male; cystektomie